2017
DOI: 10.1016/j.jacep.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Envelope Is Associated With Low Infection Rates After Implantable Cardioverter-Defibrillator and Cardiac Resynchronization Therapy Device Replacement

Abstract: Use of TYRX was associated with a lower major CIED infection rate. (TYRX™ Envelope for Prevention of Infection Following Replacement With a CRT or ICD; [Centurion]; NCT01043861/NCT01043705).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 27 publications
3
29
1
Order By: Relevance
“…Longer battery longevity, less ICD lead revisions due to lead failure and conservative management of device recalls should reduce the revision rate and consecutively the infection rate. Other forms like the use of antibacterial envelope might further reduce the infection rate …”
Section: Discussionmentioning
confidence: 99%
“…Longer battery longevity, less ICD lead revisions due to lead failure and conservative management of device recalls should reduce the revision rate and consecutively the infection rate. Other forms like the use of antibacterial envelope might further reduce the infection rate …”
Section: Discussionmentioning
confidence: 99%
“…Results from the recently published Citadel study showed a significantly lower CIED infection rate with use of an envelope compared to a previously reported rates without an envelope (0.4% vs. 2.2%, P = 0.0023) . Although these data were not included in our analysis due to the use of only a benchmark control infection rate being used as a control, the results support the findings of our meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Serious infections can lead to lethal complications such as urosepsis, wound dehiscence, and erosion at the pocket site. An FDA‐approved antibacterial envelope—a poly(propylene) mesh that releases antimicrobial agents including rifampin and minocycline (TYRX, Medtronic Inc., USA)—has shown significant efficacy in reducing the risk of infection ( Figure a) …”
Section: Soft Bioelectronics–assisted Therapymentioning
confidence: 99%